The millennials' guide to building business right a S.A.F.E.R. system to succeed in today's business world - Leez A. Hassan Dr (Adla Group Sdn Bhd, 2017)
The Millennials' Guide to Building Business Right' gives Millennials the best, proven real world applicable strategies from the minute they come up with their business idea to the actual running of their business.With over 20 years of entrepreneurial experience running three different businesses; award winning entrepreneur, author, speaker, philanthropist and mother of six - Datin Dr Leez Hassan shared her personal business knowledge and system into a book while using a unique work life balance approach into everything she does to ensure long term success and well being.